New‐Type Nickel Oxalate Nanostructures for Ultrahigh Sensitive Electrochemical Biosensing of Glucose. Issue 18 (11th August 2016) - Dong, Chaoqun; Yan, Xuejiao; Si, Conghui; Gao, Hui; Ma, Wensheng; Cheng, Guanhua; Yang, Wanfeng; Zhong, Hua; Zhang, Zhonghua
Abstract : This study reports a unique binder‐free nickel oxalate (NiC2 O4 ) nanodiamond‐decorated Ni foam which is fabricated through anodization, as a new‐type electrode material for nonenzymatic glucose biosensing. The electrode presents multilinear detection ranges with ultrahigh sensitivities (up to 144.26 mA mm −1 cm −2 ) and an ultralow detection limit (5 × 10 −9 m ), as well as acceptable selectivity and stability toward glucose detection. The superior sensing performance not only originates from the electrochemical catalytic activity of NiC2 O4 nanodiamonds, but also associates with its in situ growth on the skeleton of Ni foam, making full use of the high conductivity of the metal substrate and the direct interface contact between the two materials and concurrently promoting superior electronic/ion conductivity of the whole electrode. Besides, a new method to determine the turnover frequency is introduced to evaluate the intrinsic chemical properties of biochemical catalysts for glucose detection. This is the first attempt to systematically illustrate that nickel oxalate can also be applied to the electrochemical oxidation of glucose. More significantly, the findings can direct the fabrication of many other oxalate‐based nanostructured glucose biosensors with high performance. Abstract : A NiC2 O4 nanodiamond‐decorated Ni foam electrode is fabricated via a facile electrochemical strategy, namely anodization of Ni foam. Serving as a material for enzyme‐free glucose biosensing, the hybrid electrode exhibits multilinear detection ranges with ultrahigh sensitivities (up to 144.26 mA mm −1 cm −2 ) and an ultralow detection limit of 5 × 10 −9 m .